Positron emission tomography-computed tomography for inguinal nodes in vulvar cancer - Jorge Oldan; Stephanie Sullivan (World Journal of Nuclear Medicine)
We aimed to determine the sensitivity and specificity of fluorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) for the spread of disease to inguinal lymph nodes in vulvar cancer. A retrospective review of vulvar cancer patients who underwent both inguinal nodal sampling and dissection as well as FDG PET-CT was performed, with 21 patients meeting criteria. The sensitivity and specificity of the FDG PET-CT imaging was performed using a combination of maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG). Using an SUVmaxcutoff of 4.5 or of two times the average liver uptake, we had a 100% sensitivity and 89% specificity for positive inguinal nodes. MTV and TLG did not add to sensitivity or specificity. We conclude that FDG PET-CT has good sensitivity for inguinal nodal spread in vulvar cancer, and either a quantitative or semiquantitative approach is effective.